Evaluation of efficacy of different concentrations of newer insecticides against thrips, Scirtothrips dorsalis Hood (Thysanoptera: Thripidae) infesting castor: EVALUATION OF NEWER INSECTICIDES AGAINST THRIPS INFESTING CASTOR - F K CHAUDHARY; M K CHANDARAG; D N TEJANI; L D PARMAR; G P GANGWAR; A L JAT; A M PATEL; J R PATEL (Journal of Oilseeds Research, 2023)
Field experiment was conducted at Centre for Oilseeds Research, S.D. Agricultural University, Sardarkrushinagar, Gujarat India during 2018-2019, 2019-2020, 2020-21 and 2021-22 to evaluate the efficacy of three newer insecticides (acetamiprid 20 SP, clothianidin 50 WDG, flonicamid 50 WG) with different concentrations (lower, normal and higher dose) against thrips (Scirtothrips dorsalis) infesting castor. Based on pooled analysis of four years data, mean population of thrips were found lower in plots treated with flonicamid 50 WG @ 0.019% (36.35 thrips/tender spike/plant), flonicamid 50 WG @ 0.015% (37.57 thrips/tender spike/plant) followed by flonicamid 50 WG @ 0.011% (39.16 thrips/tender spike/plant) and acetamiprid 20 SP @ 0.004% at its normal dose recorded 40.02 thrips/tender spike/plant which are at par with each other. The treatments acetamiprid 20 SP @ 0.005% and clothianidin 50 WDG @ 0.031% observed 40.21 and 40.58 thrips/tender spike/plant, respectively. Maximum seed yield of castor was realized from the acetamiprid 20 SP @ 0.005% treated plots (2284 kg/ha) followed by flonicamid 50 WG @ 0.019% (2220 kg/ha) and flonicamid 50 WG @ 0.015% (2148 kg/ha), which were at par with each other, whereas the lowest seed yield was recorded in control (1910 kg/ha). The maximum net gain (`24945/ha) and benefit-cost ratio (1:11.50) was obtained with application of acetamiprid 20 SP @ 0.005% followed by acetamiprid 20 SP @ 0.004 % (`6245/ha and 1:3.09) and flonicamid 50 WG (`16622/ha and 1:2.84).